MAGI2 Gene Region and Celiac Disease - Jauregi-Miguel, Amaia; Santin, Izortze; Garcia-Etxebarria, Koldo; Olazagoitia-Garmendia, Ane; Romero-Garmendia, Irati; Sebastian-delaCruz, Maialen; Irastorza, Iñaki; , Spanish Consortium for the Genetics of Celiac Disease; Castellanos-Rubio, Ainara; Bilbao, Jose Ramón (Frontiers in Nutrition, 2019)
Celiac disease (CD) patients present a loss of intestinal barrier function due to structural alterations in the tight junction (TJ) network, the most apical unions between epithelial cells. The association of TJ-related gene variants points to an implication of this network in disease susceptibility. This work aims to characterize the functional implication of TJ-related, disease-associated loci in CD pathogenesis. We performed an association study of 8 TJ-related gene variants in a cohort of 270 CD and 91 non-CD controls. The expression level of transcripts located in the associated SNP region was analyzed by RT-PCR in several human tissues and in duodenal biopsies of celiac patients and non-CD controls. (si)RNA-driven silencing combined with gliadin in the Caco2 intestinal cell line was used to analyze the implication of transcripts from the associated region in the regulation of TJ genes. We replicated the association of rs6962966*A variant [p=0.0029; OR=1.88 (95%1.24-2.87)], located in an intron of TJ-related MAGI2 coding gene and upstream of RP4-587D13.2 transcript, bioinformatically classified as a long non-coding RNA (lncRNA). The expression of both genes is correlated and constitutively downregulated in CD intestine. Silencing of lncRNA decreases the levels of MAGI2 protein. At the same time, silencing of MAGI2 affects the expression of several TJ-related genes. The associated region is functionally altered in disease, probably affecting CD-related TJ genes.